Sharia certification standards: a case study of sharia certification in sharia hotels - Rasmuddin Rasmuddin; Wahyudi Umar (Borobudur Law Review, 2022)
Economic activities carried out by humans according to the Islamic view are basically the realization of the duties and functions of humans as the caliph of Allah (khalifatullah) on Earth. Economic activity is considered as a means to fulfill the course of life which not only aims to fulfill material needs in this world but is the actualization of a form of devotion to Allah SWT which leads to the hope of obtaining His pleasure in the hereafter. Sharia certification in sharia business activities is believed possibly maintain the market trust, increase competitiveness and existence in business competition. This paper intends to introduce the concept of Islamic economics and assert the standards of Sharia certification in Sharia hotel business activities. This research is normative legal research using three approaches, namely, the statute approach, the case approach, and the conceptual approach. Data is collected from books, journals, related laws, and regulations. The results of the study show that the standard of Sharia certification in business activities for Sharia hotels must comply with Sharia guidelines determined by the Indonesian Ulema Council (MUI). Sharia certification in business activities should begin with the presence of sharia certification arrangements for business activities in various laws and regulations, in the form of including provisions for sharia certification in business activities in the law on limited liability companies, the law on consumer protection, the law on Brands, or the presence of a new Law concerning Sharia Business Guarantee as the presence of Law number 33 of 2014 concerning Halal Product Guarantee.